Implementing Early Childhood Sexual Education to Prevent Child Sexual Abuse: A Case Study at RA Al-Khairaat SKEP Ternate, Indonesia: Preventing Child Sexual Abuse in Early Childhood Education - Elsa Ramadani; Yusuf Maronta; Farida Samad; Yulia Novita Sari; Bujuna A. Alhadad; Muhammad Asrun (Primary Education Insight, 2026)
Child sexual abuse is a serious global issue that requires preventive efforts starting from early childhood. This study aims to examine the implementation of early childhood sexual education as a strategy for preventing child sexual abuse at RA Al-Khairaat SKEP, Ternate, Indonesia. A qualitative case study design was used to explore how sexual education is implemented in a natural educational setting. Participants included two teachers, two parents, and two children aged 5–6 years, selected through purposive sampling. Data were collected through semi-structured interviews, participatory observation, and documentation, and analyzed using the interactive model of Miles and Huberman. The findings show that sexual education is implemented through three main aspects: self-identity recognition, gender understanding, and self-protection skills. Children were able to recognize their identities, inclusively understand gender concepts, and identify appropriate and inappropriate touch. The implementation was supported by thematic, play-based, and interactive learning approaches, as well as the integration of religious and moral values. Collaboration between teachers and parents also played an important role in reinforcing children’s understanding and protective behaviors. This study concludes that early childhood sexual education can serve as an effective preventive strategy against child sexual abuse when delivered through developmentally appropriate, culturally relevant, and collaborative approaches. The findings help bridge the gap between theory and practice and provide practical guidance for educators, parents, and policymakers in designing context-sensitive sexual education programs.